Modeling of existing cooling towers in ASPEN PLUS using an equilibrium stage method - João A. Queiroz (2012)
Simulation of cooling tower performance considering operating conditions away from design is typically based on the geometrical parameters provided by the cooling tower vendor, which are often unavailable or outdated. In this paper a different approach for cooling tower modeling based on equilibrium stages and Murphree efficiencies to describe heat and mass transfer is presented. This approach is validated with published data and with data collected from an industrial application. Cooling tower performance is simulated using ASPEN PLUS. Murphree stage efficiency values for the process simulator model were optimized by minimizing the squared difference between the experimental and calculated data using the Levenberg-Marquardt method. The minimization algorithm was implemented in Microsoft Excel with Visual Basic for Applications, integrated with the process simulator (ASPEN PLUS) using Aspen Simulation Workbook. The simulated cooling tower air and water outlet temperatures are in good accordance with experimental data when applying only the outlet water temperature to calibrate the model. The methodology is accurate for simulating cooling towers at different operational conditions.